Scientific and technological creative stage design using artificial intelligence. (October 2022) - Yang, Zhiyong
Highlights: In this manuscript, we employed Artificial Intelligence (AI) technology to perform novel research on traditional stage design in order to merge traditional Chinese opera with current intelligent technology. We concentrated on the development of scientific and technical equipment for stage design, the collaboration between intelligent technology and the establishment of opera culture, and the stage design effect and overall stage effect following the adoption of AI technology. According to the results of the performance analysis research, merging traditional Chinese opera with AI resulted in substantial performance efficiency when compared to conventional procedures. Abstract: To combine traditional Chinese opera with modern intelligent technology, we use Artificial Intelligence (AI) technology to conduct innovative research on traditional stage design. In this paper, we mainly focused on the production of scientific and technological equipment for stage design, the cooperation between intelligent technology and opera culture creation, and the stage design effect and the overall stage effect after the introduction of AI technology. We elaborate on the background of AI in traditional opera art creation space and associate it with the internet collaborative creation from multiple angles through the survey as satisfaction, staff salary difference, calculation comparison, etc. The performance analysis study reveals that combining traditional Chinese opera with AI resulted in significant performance efficiency compared to conventional techniques.